Benign mosaic chromosomal structural variants across generations: evidence for a developmental correction mechanism from clinical and computational models - Ruan, Jiayu; Song, Qinhao; Hu, Yue; Liu, Xiaodan; Li, Suping; Zhu, Jianjun; Yang, Li (Frontiers in Genetics, 2025)
ObjectiveThis study investigates the intergenerational transmission of benign mosaic supernumerary marker chromosomes or structural variant chromosomes (SMCs/SVs) and explores the developmental mechanisms that maintain non-pathogenic mosaic levels across generations. While chromosomal mosaicism is widely recognized in reproductive genetics, most previous work has focused on pathogenic outcomes. Here, we highlight an underexplored phenomenon of non-pathogenic SMCs/SVs mosaicism and propose a developmental selection model that may explain its stable inheritance.MethodsWe describe a rare father–offspring pair carrying a mosaic SV at chromosome 11p11, both phenotypically normal. Karyotyping and SNP-array analyses were performed on parental blood, amniotic fluid, and cord blood. A systematic literature review identified 35 additional families with benign parent–child SMCs/SVs mosaicism. To probe potential regulatory mechanisms, four complementary computational approaches including agent-based simulation, logistic regression, Bayesian inference, and Markov chain modeling were applied to evaluate the developmental selection dynamics.ResultsThe father exhibited a 57% SV mosaic ratio, while the offspring showed comparable or slightly reduced ratios (38%–45%). Literature analysis revealed consistent patterns of equal or lower mosaicism in offspring across diverse SMCs types, suggesting that transmission occurs within a constrained, non-pathogenic range. Computational modeling demonstrated that even mild negative selection during blastocyst development could reproduce these retention trends, supporting a developmental selection mechanism that limits SMCs/SVs-positive cells to a harmless threshold.ConclusionThese findings provide convergent clinical and computational evidence that early human embryos may employ a self-correction mechanism to regulate benign SMCs/SVs mosaicism. We propose a developmental “Shepherd Mechanism,” whereby mosaic cells are selectively eliminated until a safe equilibrium is reached, ensuring viable yet non-pathogenic inheritance. This work introduces a conceptual framework for understanding naturally tolerated chromosomal variation and offers theoretical guidance for prenatal genetic counseling and embryo selection strategies in assisted reproduction.